COVID-19 Vaccination Does Not Affect Reproductive Health Parameters in Men - Reschini, Marco; Pagliardini, Luca; Boeri, Luca; Piazzini, Francesca; Bandini, Veronica; Fornelli, Gianfranco; Dolci, Carolina; Cermisoni, Greta Chiara; Viganò, Paola; Somigliana, Edgardo; Coccia, Maria Elisabetta; Papaleo, Enrico (Frontiers in Public Health, 2022)
With the implementation of COVID-19 vaccine up-take, doubts regarding the impact of immunization on future fertility have begun to emerge. We have examined vaccine safety on male reproductive health. We set up a multicentre (three infertility centers), retrospective study in order to assess semen parameters and fertilization rate of one hundred-six men in a pairwise comparison between the first and second assisted reproduction technology (ART) attempt, performed respectively before and after COVID-19 vaccination. Median time (range) between the first vaccine dose and the second ART cycle was 75 days (39–112). Semen parameters did not change before and after the exposure. Fertilization rate was also similar before and after vaccination. Twenty-five patients (24%) were oligozoospermic before the vaccination while 26 (25%) after the exposure (P = 0.87). Severe asthenozoospermia were present in 11 patients before as well as after the exposure. No difference was observed even after considering different types of vaccines (mRNA or viral vector). COVID-19 vaccination did not affect sperm quality and fertilization capacity of men undergoing ART treatments and should be considered safe for men's reproductive health.